STUDENTS’ INTEREST IN READING SHORT STORY AT GRADE IX SMP NEGERI 3 SAMATURU KABUPATEN KOLAKA - Agus Nasir (Journal of Indonesian Language Education and Literary, 2017)
This research is a descriptive study that aims to get an idea of the interest in reading short story at the students of SMP Negeri 3 Samaturu Kolaka. Overall respondents are students of class IX SMP Negeri 3 Samaturu totaling 65 people. The data collection technique used was to spread the Likert scale questionnaire to the respondents. The questionnaire contains 20-point declarations, which consisted of 13 items of positive statements and 7 negative items. The data obtained in this study were processed and analyzed by scoring and coding techniques and result showed that 4 respondents or 6.15% of respondents who have a low interest in reading; 29 respondents or 44.62% of respondents who have a moderate interest in reading; 32 respondents or 49.23% of respondents who have a high interest in reading. Based on the criteria used, interest in reading short stories of grade IX students of SMP Negeri 3 Samaturu said to be sufficient if the percentage of respondents reading interest category is being increased percentage of respondents’ categories of high interest to reach 60% or more. Therefore, the percentage of respondents reading interest categories plus the percentage of respondents currently high interest categories reached 93.85%, it was concluded that the students' interest in reading short stories at grade IX SMP Negeri 3 Samaturu Kolaka was adequate.